2017
DOI: 10.3389/fpsyg.2017.00018
|View full text |Cite
|
Sign up to set email alerts
|

Coping Strategies in Liver Transplant Recipients and Caregivers According to Patient Posttraumatic Growth

Abstract: The purpose of this study was to analyze the differences in coping strategies employed by liver transplant recipients and their family members according to patient posttraumatic growth. Two matched groups of 214 liver transplant recipients and 214 family members were selected. The Posttraumatic Growth Inventory and Brief COPE were used. The most relevant results were: (1) Interactive effects in active coping, support (instrumental and emotional) and acceptance strategies, which were all used more by patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(44 citation statements)
references
References 39 publications
1
42
1
Order By: Relevance
“…While quality of life improves after transplant, participants of the present study described ongoing issues associated with mental health and emotional resilience that may impact on health‐related decision making . Unique emotional stressors such as survivor guilt and post‐traumatic stress are recognised in organ transplant recipients . Study participants indicated that before they could address their diet and exercise needs, they needed better strategies to cope with the insecurity and uncertainty associated with survival; and also needed the physical and emotional resources to deal with their current medical issues.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…While quality of life improves after transplant, participants of the present study described ongoing issues associated with mental health and emotional resilience that may impact on health‐related decision making . Unique emotional stressors such as survivor guilt and post‐traumatic stress are recognised in organ transplant recipients . Study participants indicated that before they could address their diet and exercise needs, they needed better strategies to cope with the insecurity and uncertainty associated with survival; and also needed the physical and emotional resources to deal with their current medical issues.…”
Section: Discussionmentioning
confidence: 91%
“…You know what I mean you can have all these people tracking you and following you and advising you but if you don't take that responsibility and own it, it doesn't work'. (FG,20) Back to Life Participants described a renewed outlook on life and expressed their desire to return to 'normality' and 'stability'. The word 'life' was used in the context of rebuilding life, getting back to 'normal' life, 'making the most of life' and social life.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Scarce literature exist on housewives as a group. There has been a traditional lack of recognition of their labor or the associated psychosocial risks, among them stress and burnout (Pascual, 2001). However, the work they perform in the home, the number of family members they live with, and attention to minors or family members with health problems cause an effect similar to the working conditions under rotating shifts or night jobs, and overwork perceived in other professions.…”
Section: Introductionmentioning
confidence: 99%